Virus infections in tumors pave the way for tumor-directed DC-vaccines - Woller, Norman (Landes Bioscience, 2012)
Effective treatment of solid cancers by tumor-directed DC-vaccines still remains a challenge in clinical oncology. For therapeutic success, knock-down of tumor-specific tolerance appears mandatory before a potent tumor-specific cytotoxic T-cell response can be triggered by DC-vaccinations. Evidence is emerging that lytic virus infection in tumors can provide valuable help.